If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4y + -2) = 3(5 + 3y) Reorder the terms: 6(-2 + 4y) = 3(5 + 3y) (-2 * 6 + 4y * 6) = 3(5 + 3y) (-12 + 24y) = 3(5 + 3y) -12 + 24y = (5 * 3 + 3y * 3) -12 + 24y = (15 + 9y) Solving -12 + 24y = 15 + 9y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-9y' to each side of the equation. -12 + 24y + -9y = 15 + 9y + -9y Combine like terms: 24y + -9y = 15y -12 + 15y = 15 + 9y + -9y Combine like terms: 9y + -9y = 0 -12 + 15y = 15 + 0 -12 + 15y = 15 Add '12' to each side of the equation. -12 + 12 + 15y = 15 + 12 Combine like terms: -12 + 12 = 0 0 + 15y = 15 + 12 15y = 15 + 12 Combine like terms: 15 + 12 = 27 15y = 27 Divide each side by '15'. y = 1.8 Simplifying y = 1.8
| 10x+17=67 | | -6x-7=53 | | -3x+7=-5-3 | | -5/8x=20 | | 2x-2/5-x-2/2=0,7x | | 2x+39=9x+31 | | 7y/3+11=9y/4+15 | | -2-2=-16 | | 2x+39=5x-13 | | x+(-1/5)=3/5 | | 3w=4.2 | | 4x+3+x=23 | | 7v=79 | | 20z^2+27z-8= | | (-2/3)(6) | | 6w+3+3w=17 | | 7/9+(-7/9) | | -2x-5+5=-5 | | p/-8-7=-11 | | 12e-19=-7-e | | w/3+8=5 | | 12+m/7=15 | | 1.2x+4.3=2.1 | | b/3+8=13 | | 14=u/4-(-9) | | y/9-4=6 | | -11+z/5=-7 | | 0.4(x+80)+0.6x=57 | | (8x+9)(5x+2)=0 | | 9x^2+-11x=5x | | 4+17t-2=8t+128-5t | | -2a+5=11 |